2013
DOI: 10.1007/s13762-013-0417-7
|View full text |Cite
|
Sign up to set email alerts
|

Jet loop reactor application for mine water treatment using fly ash, lime and aluminium hydroxide

Abstract: Recent studies have shown that a combination of coal fly ash (FA) and Al(OH) 3 can be used to treat neutral mine drainage (NMD) and reduce sulphate concentration to within South African drinking water quality levels, Class II (400-600 mg/L). The shortcomings of this method were the large amounts of FA required to raise the pH to greater than 11 (3:1 liquidto-solid ratio) so that Al(OH) 3 can be added to facilitate removal of sulphate ions through ettringite precipitation. This requires large silos to store FA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 12 publications
1
19
1
Order By: Relevance
“…It is also a huge problem in the Mpumalanga coalfields. The few freshwater resources in Mpumalanga including the Vaal and Olifants rivers are threatened by AMD containing a high concentration of sulfate ions, Al, Fe, and Mn (Madzivire et al, 2015). The protection of water resources has become a fundamental policy concern as well as a driver for continued economic growth and service delivery to South Africa (Oberholster et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also a huge problem in the Mpumalanga coalfields. The few freshwater resources in Mpumalanga including the Vaal and Olifants rivers are threatened by AMD containing a high concentration of sulfate ions, Al, Fe, and Mn (Madzivire et al, 2015). The protection of water resources has become a fundamental policy concern as well as a driver for continued economic growth and service delivery to South Africa (Oberholster et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The jet loop reactor promotes a faster reaction rate by exerting a higher mass transfer rate and mixing intensity compared to a continuous stirred tank reactor. A high mixing rate in a jet loop reactor occurs due to hydrodynamic cavitation and impingement processes that occur inside the reactor (Vadapalli et al, 2008;Madzivire et al, 2015). Hydrodynamic cavitation is created by pressure variations due to the changes in the geometry of the system through which the solution is flowing.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrodynamic cavitation is applied on a pilot plant scale within a jet loop reactor. In a study involving the scaling-up of a process to reduce sulphate concentrations within neutral mine drainage, a jet-loop reactor was used [69]. The study showed that the impingement and cavitation mixing techniques applied within the jet-loop reactor played an important role in enhancing the sulphate removal.…”
Section: Synthesis Of Zeolites From Coal Fly Ashmentioning
confidence: 99%
“…African drinking water quality levels (Madzivire et al, 2015). The pH was raised to greater than 11 by mixing lime (w/v ratio) with fly ash, and then amorphous Al(OH)3 was added to reduce sulfate concentration to less than 500 mg/L.…”
Section: Treatment Optionsmentioning
confidence: 99%